ANALISIS MOTIVASI BEROLAHRAGA PADA MASYARAKAT DI KOTA PALOPO - Nurdin, Muh Nur Ihlas; Ahmad; Hidayat, Rachmat; Nur, Suaib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the motivation of Palopo City residents to participate in sports activities. Regular physical activity plays a vital role in maintaining physical and mental health, yet levels of sports participation in various regions, including Palopo City, vary. This study employed a quantitative approach with a survey method distributed to 100 respondents from various age groups, genders, and occupations. Data were analyzed using descriptive and inferential statistics to identify factors influencing exercise motivation, such as intrinsic motivation (health, fitness, enjoyment) and extrinsic motivation (physical appearance, social pressure, facilities). The results showed that the majority of residents were motivated by health and fitness factors, while facilities and the social environment also had significant influences. These findings are expected to serve as a basis for local governments and relevant agencies in designing more targeted and sustainable sports programs.